Investment Attractiveness. The Case Of The Visegrad Group Countries - Dorożyński, Tomasz; Kuna-Marszałek, Anetta (Comparative Economic Research. Central and Eastern Europe, 2016)
In the article, we attempt to assess the investment attractiveness of the New EU Member States, using the Visegrad Group countries as examples. This study is structured as follows: First, it explores the existing literature on factors of investment attractiveness. Further we examine inward foreign direct investment flows in the Visegrad Group countries against the global performance in the area from 1990 to 2013. Next we discuss the investment attractiveness of New Member States of the European Union in selected international rankings, paying special attention to the positions occupied by the four analysed countries. The final part examines the correlation between selected variables characteristic of investment attractiveness and the inflow of foreign investment. The study is based on statistical methods (Spearman’s rank correlation and Pearson correlation). At the end we present our conclusions.